Corrosion Inhibitor of Mild Steel by Polar Extract of Theobroma cacao Peels in Hydrochloric Acid Solution - Yetri, Yuli; Emriadi; Jamarun, Novesar; Gunawarman (Asian Journal of Chemistry, 2015)
In order to decrease corrosion attack of hydrochloric acid on mild steel, Theobroma cacao peels polar extract was added as a corrosion inhibitor. Corrosion behavior of the metal was investigated using static accelerated corrosion tests including weight loss method and electrochemical polarization. A mild steel containing 0.3 % carbon is exposed in 1.5 M HCl solution with 0 to 2.5 % of the Theobroma cacao polar extract for 48 to 768 h at room temperature (298 K). The solution was also heated 303 to 323 K for 192 h to obtain inhibition efficiency under higher working temperatures. Morphology of sample surfaces was examined by scanning electron microscope. While, the adsorbed film on mild steel surface was measured by Fourier transform infrared spectroscopy. The corrosion test results showed that the inhibition efficiency increases significantly up to 96 % with increasing of Theobroma cacao polar extract content. However, the inhibition efficiency decreases slightly with the increase of temperature. The inhibition mechanism of Theobroma cacao polar extract on the mild steel surface is mainly chemical adsorption where Theobroma cacao polar extract donates a pair of electrons to make a coordination covalent bond with Fe2+ ions and then results organometallic compound on the mild steel surface. Surface condition is then improved due to the adsorption, for forming the corrosion protection. The addition of Theobroma cacao polar extract into HCl is very effective to reduce corrosion attack on the mild steel.